Women Wage Earning and Education in Rural Nigeria (2014)
Determining how women's education affects their wage earnings is remarkably important in today's society where women are increasingly entering the labor market. Human Capital Theory suggests that women who acquire more education earn more than women who have less education. Using a sample of 48067 women from Harmonised National Living Standard Survey 2010 data collected by Nigeria Bureau of Statistics in 2009/2010, an Heckman model was used to examine the effect of education on women wage earning. It was revealed that the higher the level of education, the higher the wage accruing to individual women in rural Nigeria. The study suggested that women should Le encouraged to attend school and when it is necessary try to convince them to obtain higher degree of education